Socioeconomic status, human papillomavirus, and overall survival in head and neck squamous cell carcinomas in Toronto, Canada. (February 2016) - Chu, K.P.; Habbous, S.; Kuang, Q.; Boyd, K.; Mirshams, M.; Liu, F.-F.; Espin-Garcia, O.; Xu, W.; Goldstein, D.; Waldron, J.; O'Sullivan, B.; Huang, S.H.; et al.
Highlights: We assess head and neck cancer survival and area-level socioeconomic status. The role of anatomic subsite and human papillomavirus was considered. Area-level socioeconomic status was associated with worse overall survival. Age, sex, tumor stage, and smoking/alcohol were more important prognostic factors. Socioeconomic status was associated with risk and prognostic factors. Abstract: Background: Despite universal healthcare in some countries, lower socioeconomic status (SES) has been associated with worse cancer survival. The influence of SES on head and neck cancer (HNC) survival is of immense interest, since SES is associated with the risk and prognostic factors associated with this disease. Patients and methods: Newly diagnosed HNC patients from 2003 to 2010 ( n = 2124) were identified at Toronto's Princess Margaret Cancer Centre. Principal component analysis was used to calculate a composite score using neighbourhood-level SES variables obtained from the 2006 Canada Census. Associations of SES with overall survival were evaluated in HNC subsets and by p16 status (surrogate for human papillomavirus). Results: SES score was higher for oral cavity ( n = 423) and p16-positive oropharyngeal cancer (OPC, n = 404) patients compared with other disease sites. Lower SES was associated with worse survival [HR 1.14 (1.06–1.22), p = 0.0002], larger tumor staging ( p < 0.001), current smoking ( p < 0.0001), heavier alcohol consumption ( p < 0.0001), and greater comorbidity ( p < 0.0002), but not with treatment regimen ( p > 0.20). After adjusting for age, sex, and stage, the lowest SES quintile was associated with the worst survival only for OPC patients [HR 1.66 (1.09–2.53), n = 832], primarily in the p16-negative subset [HR 1.63 (0.96–2.79)]. The predictive ability of the prognostic models improved when smoking/alcohol was added to the model ( c -index 0.71 vs. 0.69), but addition of SES did not ( c -index 0.69). Conclusion: SES was associated with survival, but this effect was lost after accounting for other factors (age, sex, TNM stage, smoking/alcohol). Lower SES was associated with greater smoking, alcohol consumption, comorbidity, and stage.